Influence of Different Levels of GA3 and Urea on Fruiting Behavior, Yield and Qualitative Characters of Ber (Zizyphus mauritiana Lamk.) cv. Banarasi Karaka - Kumar, Adesh; Tripathi, V. K.; Awasthi, Manuj; Pandey, Shiwanand (International Journal of Bio-resource and Stress Management, 2024)
The present experiment was conducted during October, 2022 to March, 2023 at Horticulture Garden, Department of Fruit Science of Chandra Shekhar Azad University of Agriculture and Technology, Kanpur, U.P, India. The experiment was layout in RBD with three replicates of each treatment. Total 10 treatments including one control viz., GA3 15 ppm, GA3 20 ppm, GA3 25 ppm, GA3 30 ppm, Urea 2%, GA3 15 ppm and urea 2%, GA3 20 ppm and urea 2%, GA3 25 ppm and urea 2%, GA3 30 ppm and urea 2% and Control i.e., water spray. The present investigation, it is reported that the application of GA3 30 ppm and Urea 2% with significantly increased initial fruit set (169), fruit retention (84.22%) and decreased fruit drop (84.22%), increased fruit weight (15.44 g), pulp weight (14.43 g), fruit length (4.52 cm), diameter (2.99 cm), volume (16.80 cc) and yield (31.50 kg) branch-1 and minimum stone weight (1.01 g), pulp: stone ratio (14.29) and quality parameters like; TSS (15.30 °Brix), ascorbic acid (99.25 mg) 100 g-1 of fruit pulp and total sugars (9.99%) and decreased titratable acidity (0.10%) content. Hence, plants treated with GA3 30 ppm and urea 2% can further be used to improve the fruiting, overall yield improvement, and quality characteristics of Banarasi Karaka cultivar of ber.